2016
DOI: 10.15226/2374-6890/3/6/00162
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Glycemic Control among Type 2 Diabetes Patients Attending Mathari National Teaching Hospital, Nairobi Kenya

Abstract: Introduction: Type 2 Diabetes mellitus is chronic metabolic disorder characterized by hyperglycemia resulting from insulin secretion, insulin action, or both and accounts for over 95% cases globally. Uncontrolled diabetes may result to complications (retinopathy, nephropathy, neuropathy leading to amputations, stroke, heart attack and sexual dysfunction), glycated hemoglobin below 7.0% is recommended for good prognosis.The study determined factors associated with glycemic control, among T2DM patient attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
4
17
4
Order By: Relevance
“…This raises concern as poorly controlled diabetes puts the patients at risk of complications [38]. Other studies on T2DM patients have reported even a lower proportion of patients with controlled HbA1c [38][39][40]. The results on the effect of mobile phone communication in this study are similar to those made in other studies [41][42][43] where the communication did not have a significant effect.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This raises concern as poorly controlled diabetes puts the patients at risk of complications [38]. Other studies on T2DM patients have reported even a lower proportion of patients with controlled HbA1c [38][39][40]. The results on the effect of mobile phone communication in this study are similar to those made in other studies [41][42][43] where the communication did not have a significant effect.…”
Section: Discussionsupporting
confidence: 84%
“…The proportion of subjects with well-controlled HbA1c was relatively low in both the intervention and control groups, and mobile phone communication did not have a significant effect in the control. This raises concern as poorly controlled diabetes puts the patients at risk of complications [38]. Other studies on T2DM patients have reported even a lower proportion of patients with controlled HbA1c [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study showed that the level of glycemic control among type II diabetic patients is 71.4% which is consistent with the finding at Dessie Referral Hospital (70.8%), Jimma University Teaching Hospital (70.9%), Turkey (67.5), Myanmar (72.1%), and Saudi Arabia (74.9%) [ 12 , 20 , [30] , [31] , [32] ]. On the other hand, it is below than the study conducted at Tikur Anbessa Hospital (80%), South Africa (83.8%), Kenya (81.6%), India (91.8%), and Palestine (80.5%) [ [33] , [34] , [35] , [36] , [37] ]. On the other hand, it is higher than the study done at Zambia (61.3%), Limmu Genet Hospital (63.8%), Suhul Hospital (63.5%), Nigeria (55%), Ayider Specialized hospital (48.7%) and Shenen Gibe Hospital (59.2%) [ 21 , [38] , [39] , [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 80%
“…Diabetes self-management education complements diabetes medication, which has failed to control blood glucose despite its accessibility and proven efficacy in many type 2 diabetic patients (HBA1c ≤ 6.5%). An estimated 80% of type 2 diabetes patients in Kenya 5 and Cape Town, South Africa, respectively 6 have poor glycaemic control contributing to an increase in diabetes complications. This increase necessitates effective diabetes prevention and control measures including DSME, especially noting that a 1-point improvement of HbA1c is associated with a 20% and 30% – 40% decrease in macro-vascular and micro-vascular complications, respectively.…”
Section: Introductionmentioning
confidence: 99%